2021
DOI: 10.3390/cancers13071727
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Anaplerosis Has an Onco-Driving Potential in Prostate Cancer Cells

Abstract: Tumor cells display metabolic alterations when compared to non-transformed cells. These characteristics are crucial for tumor development, maintenance and survival providing energy supplies and molecular precursors. Anaplerosis is the property of replenishing the TCA cycle, the hub of carbon metabolism, participating in the biosynthesis of precursors for building blocks or signaling molecules. In advanced prostate cancer, an upshift of succinate-driven oxidative phosphorylation via mitochondrial Complex II was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Untargeted metabolomics is a "hypothesis-generating discovery strategy" that compares different groups of samples (e.g., cancer vs. controls) [26], which is a promising approach to identify novel metabolic markers. This strategy has been applied recently in PCa [19,27]. Thus, the combination of ultra-high-performance liquid chromatography with high-resolution mass spectrometry (UHPLC-HRMS) and epidemiological approaches may open new perspectives in PCa research, enabling the identification of novel biomarkers for evaluating the future risk of PCa, and the investigation of the etiology of PCa [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics is a "hypothesis-generating discovery strategy" that compares different groups of samples (e.g., cancer vs. controls) [26], which is a promising approach to identify novel metabolic markers. This strategy has been applied recently in PCa [19,27]. Thus, the combination of ultra-high-performance liquid chromatography with high-resolution mass spectrometry (UHPLC-HRMS) and epidemiological approaches may open new perspectives in PCa research, enabling the identification of novel biomarkers for evaluating the future risk of PCa, and the investigation of the etiology of PCa [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that abnormal metabolism of succinate from the tumor environment has an anaplerotic effect that enhances the malignant potential of PCa cells ( 12 ). Succinate is the most important substrate for lysine succinylation modification.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, enhanced succinate oxidation by SDH has been identified as an emergent hallmark of PCa metabolism [9][10][11] . Increased reliance on succinate in response to reduced Complex I (CI) activity is also not unique to cancer, as cell-permeable succinate has been shown to overcome CI dysfunction in models of mitochondrial disease 34 .…”
Section: Discussionmentioning
confidence: 99%